FRI0643 Enthesitis and foot disability in patients with ankylosing spondylitis. (15th June 2017) - Serce, A; Bal, A; Dulgeroglu, D; Cakci, A
Abstract : Background: Enthesitis is a primary clinical feature of ankylosing spondylitis (AS). Lower extremity enthesopathy may cause foot pain and functional disability. Detection of enthesitis by using physical examination may be insufficient. Musculoskeletal ultrasonography is a noninvasive and low-cost method for detecting enthesitis readily. Objectives: The aims of this study were to evaluate enthesitis by using musculoskeletal ultrasonography and foot disability in patients with AS, to compare healthy controls, and to determine the correlation of enthesitis score and foot function with disease activity and functional status. Methods: In this study, 101 patients with AS and 42 healthy controls were examined for enthesal site abnormalities by using gray-scale ultrasonography. The findings were assessed by using the Glasgow Ultrasound Enthesitis Scoring System (GUESS). The foot function index (FFI), which comprised of pain, disability, and activity limitation subscales, was measured in all the patients with AS and healthy controls for assessment of foot function. Disease activity and functional status were assessed using the Bath AS Disease Activity Index (BASDAI) and Bath AS Functional Index (BASFI), respectively, in patients with AS. Results: The median GUESS score was 8.00 (1.00–23.00), and, the median total FFI and scores in all the pain, disability, and activity limitation subscales were 14.70 (0.00–75.20), 16.60 (0.00–82.80), 16.10 (0.00–84.40), and 4.00 (0.00–60.00), respectively in patients with AS. The GUESS score, total FFI, and all the subscales scores were significantly higher in the patients with AS than in the controls (p=0.00). GUESS score showed no correlation with BASDAI and BASFI. In patients with AS, total FFI and scores for all subscales showed positive correlations between BASDAI and BASFI, respectively (p=0.00, r =0, 66; p=0.00, r =0, 0, 50; p=0.00, r =0, 59; p=0.00, r =0, 31; p=0.00, r =0, 60; p=0.00, r =0, 54; p=0.00, r =0.57; p=0.00, r =0.50). Conclusions: The severities of enthesitis and foot disability were higher in patients with AS. Patients with AS may undergo ultrasonographic examination for enthesal foot involvement. Foot disability is related with disease activity and function. Foot involvement and disability should be evaluated comprehensively and managed properly. References: Balint PV, Kane D, Wilson H, McInnes IB, Sturrock RD. Ultrasonography of enthesal insertions in the lower limb in spondyloarthropathy. Ann Rheum Dis 202;61:905–910. Borman P, Koparal S, Babaoğlu S, Bodur H. Ultrasound detection of entheseal insertions in the foot of patients with spondyloarthropathy. Clin Rheumatol 2006;25:373–377. Disclosure of Interest: None declared